1992
DOI: 10.1021/jm00081a024
|View full text |Cite
|
Sign up to set email alerts
|

A novel class of enkephalinase inhibitors containing a C-terminal sulfo group

Abstract: A new series of sulfonic acids were synthesized and tested for their enkephalinase inhibitory activity. Among them, the most potent was N-(2-benzyl-3-mercaptopropionyl)metanilic acid 10i with an IC50 value of 0.27 nM. Several other analogues (10a,b,j,n,o,gg,hh) showed the inhibitory activity comparable to or greater than thiorphan (IC50 = 2.6 nM), a C-terminal carboxyl-containing inhibitor of enkephalinase. Thus compounds containing a C-terminal sulfo group, instead of the C-terminal carboxyl group, were found… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

1992
1992
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 1 publication
1
8
0
Order By: Relevance
“…Furthermore, the observation that both wild-type enzyme and N542G mutant are inhibited by S448 with similar IC50 values is consistent with our hypothesis that the NH proton of the P2' residue interacts with Asn542. All these results are consistent with the findings of other authors who observed that the replacement of the hydrogen from the NH group of the P2' residue by a methyl or cyclopropyl group produced a dramatic loss of inhibitor binding [51][52][53][54][55].…”
Section: Discussionsupporting
confidence: 93%
“…Furthermore, the observation that both wild-type enzyme and N542G mutant are inhibited by S448 with similar IC50 values is consistent with our hypothesis that the NH proton of the P2' residue interacts with Asn542. All these results are consistent with the findings of other authors who observed that the replacement of the hydrogen from the NH group of the P2' residue by a methyl or cyclopropyl group produced a dramatic loss of inhibitor binding [51][52][53][54][55].…”
Section: Discussionsupporting
confidence: 93%
“…General Procedure for the Synthesis of 2-Alkylacrylic Acids ( 4a − f ) . 2-Alkylacrylic acids 4a − f were prepared from dimethyl malonate according to a literature procedure ( ). Dimethyl malonate (44 mmol) and sodium methoxide (88 mmol) in methanol (100 mL) were refluxed for 20 min and the proper alkyl iodide (30 mmol) in methanol (50 mL) was added.…”
Section: Methodsmentioning
confidence: 99%
“…Starting from these considerations, the aim was to fight the appearance of the "stress"-related expression of microcontractions and wrinkles. Unfortunately, enkephalins exhibit a very short lifetime (about 20 seconds), because the enkephalinase enzymes rapidly destroy them [122]. Thus, intending to extend the lifetime of enkephalins, NUXE performed a screening of 165,000 plants, identifying those containing a sufficient amount of pentagalloyl glucose (PGG)-the molecule able to inhibit the activity of enkephalinases [123][124][125].…”
Section: Discovering Neurocosmetic Ingredients From Plant Extractsmentioning
confidence: 99%